PEMBERDAYAAN UKM KERUPUK SINGKONG MELALUI DIVERSIFIKASI PRODUK - Nurhartadi, Edhi; Muhammad, Dimas Rahadian Aji; Nursiwi, Asri (LPPM UNS, 2016)
Magelang regency is the center of cassava in Central Java. One of the villages in the subdistrict Kajoran whose people business are processing cassava into cassava crackers is Sidowangi village. Crackers processing is still done traditionally method. Equipment used were not conform with the standards for the food industry. It is known with the washing cassava peel in the form of a big tub filled with water, put peeled cassava, then washed by hand and foot. In order to clean cassava should be washed one by one so it takes a long time. Besides that the drying process is also done by uncontrolled because the sun drying with braids pedestal. If there is no sun the people can not drying the cassava crackers. Consequently crackers that have been damaged due to slicing become moldy or rotten and it can not be used. As an effort to resolve these problems, the UNS team has agreed with the SME partners to organize a program of activities: training and introduction liquid waste treatment technology into nata de cassava; Introductions production process technology mocaf as product diversification efforts; The introduction of appropriate technology cassava crackers processing food industry standards.The results show that the mplementation of the training activity making nata de cassava, Implementation of the training activity mocaf processing technology, Introduction Equipment For Improved Quality Cassava Crackers and Potential Product Diversification, entrepreneurial training and management of food industry, Pelatihan pemasaran berbasis IT dan strategi direct sellingKey words: diversification, crackers, cassava, introduction, technology